Enzootic bovine haematuria: a disease of concern in the hilly regions - Gurav, Amol; Jana, C; Gautam, S; Dangi, S S (Indian Farming, 2018)
Bracken fern is one of the most common weed of our ecosystem and is a major animal health concern because of its special chemical constituents. Fern has thiaminase enzyme and other thermostable organic molecule of antithiamin character. It showed characteristic neurological symptoms in monogastric bracken fern fed animals. Horses are very susceptible to bracken fern poisoning. Cardiac problems in pigs, biochemical blood changes and carcinomas in rabbit and guinea pig were observed. Bracken fern causes EBH in ruminants,characterized by blood in urine and tumors in alimentary tract and urinary bladder. It also causes bonemarrow suppression with change in blood composition. Responsible component for the effect is norsesquiterpene glycoside ptaquiloside and products of its decomposition. Different carcinomas types are common findings and are generally caused by some immunosuppressant and or mutagen substance (quercetin) of bracken fern.